2018
DOI: 10.12681/mms.2153
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of small-scale fisheries in the Adriatic Sea

Abstract: The main aim of the present study is to increase the knowledge on the seasonal dynamics of the set gears used by Adriatic small-scale fisheries (SSFs) through the collation of data (landings, fishing effort, composition of catches, length-frequency distributions of target species and economic value of landings) on target species,. The study focused on the three set gears mainly used in the basin: gillnets, trammel nets and traps. The results confirmed that SSFs are diverse, complex and dynamic, representing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…First, we emphasize the research work of Cobani et al [36] that reported a study by the FAO AdriaMed Working Group on small-scale fisheries (SSFs), which has identified the gaps and priorities for the fisheries sector in the observed region. This research is followed up by the recent scientific work of Grati et al [37] that considered the seasonal dynamics of the set gears. They observed regional small-scale fisheries including Montenegro and collected the data (landings, fishing effort, the composition of catches, and length-frequency distributions of target species and economic value of landings) on target species.…”
Section: Fisheries and Mariculturementioning
confidence: 99%
“…First, we emphasize the research work of Cobani et al [36] that reported a study by the FAO AdriaMed Working Group on small-scale fisheries (SSFs), which has identified the gaps and priorities for the fisheries sector in the observed region. This research is followed up by the recent scientific work of Grati et al [37] that considered the seasonal dynamics of the set gears. They observed regional small-scale fisheries including Montenegro and collected the data (landings, fishing effort, the composition of catches, and length-frequency distributions of target species and economic value of landings) on target species.…”
Section: Fisheries and Mariculturementioning
confidence: 99%
“…They are characterized by a diversity of target species, gear, and fishing tactics. As a result, this activity is very variable in time and space (Farrugio & Le Corre 1993;García-Rodríguez et al, 2006;Maynou et al, 2013;Moutupoulos et al, 2014;Grati et al, 2018). Despite the fact that SSFs are a primordial activity around the Mediterranean, including within Marine Protected Areas (MPAs) (Francour et al, 2001), the diversity and the great variety of their métiers create great uncertainty from the perspective of the protection and sustainable management of marine resources.…”
Section: Artisanal Small-scale Fisheries and The Mediterranean Mpasmentioning
confidence: 99%
“…Small-scale fishers (SSF) along the Mediterranean coast operate with a variety of fishing gears on a seasonal basis, and catches are composed of a wide range of species [7]. Although the European lobster, Homarus gammarus, is not a target species of SSF, it is often a bycatch in gillnets targeting different fish and other marine organisms [8][9][10].…”
Section: Introductionmentioning
confidence: 99%